The Concept of Ah (Sigh) in the Ghazals of Nabi - Ozyurek, Dursun (ILEM, 2017)
Nabi, who is one of the most productive poet of classical Turkish literature, used the conception of ah (sigh) with its various meanings in his ghazals (Ottoman lyric poetry). This article aims to determine and classify those different meanings. Thus, it is determined that there are eleven different meanings in Nabi's ghazals. These usages can be put in order in this way: The usage of ah in the meaning of whimper, the usage of ah in the meaning of similitude, the usage of ah in the meaning of the relation of action-reaction, the usage of ah in the fact of cause and occasion, the usage of ah in the meaning of personification and subject, the usage of ah in the fact of analogy, the usage of ah in the fact of threat, the usage of ah in the meaning of interjection and exclamation, the usage of ah in the meaning of advice, the usage of ah with regard to spelling in itself, the usage of ah in the fact of damn. With this article, these various meanings will be explain with couplets and there will be some information about the conception of ah and literary style of Nabi in the beginning.
Keywords: Classical Turkish literature; ghazal; Nabi; the conception of ah (sigh, groan); the usage of ah; Social Sciences - Other Topics